MANAGEMENT OF A 71-YEAR-OLD PATIENT WITH COPD EXACERBATION, BRONCHIECTASIS, AND PSEUDOMONAS AERUGINOSA COLONIZATION – CASE REPORT - Wiktor Golus; Katarzyna Andrzejewska; Paweł Edyko; Bartosz Golis; Zuzanna Przybyła; Hubert Woźniak; Anna Gęsińska; Krystian Czyżykowski; Alicja Babula; Helena Szelka (International Journal of Innovative Technologies in Social Science, 2025)
Chronic Obstructive Pulmonary Disease (COPD) frequently coexists with non-cystic fibrosis bronchiectasis (NCFB), creating a clinical overlap associated with persistent airway infection, frequent exacerbations, and accelerated functional decline. Among pathogens, Pseudomonas aeruginosa colonization confers a particularly unfavorable prognosis. We report a 71-year-old male admitted with severe dyspnea and productive cough with purulent sputum. Baseline arterial blood gases confirmed type II (hypercapnic) respiratory failure. Chest radiography excluded new focal consolidations. Bronchoscopy revealed abundant purulent secretions; bronchoaspirate culture grew P. aeruginosa susceptible to meropenem and colistin. In line with current practice and GOLD 2025 principles for acute exacerbation management, the patient received targeted antimicrobial therapy, short-acting bronchodilators, a short course of systemic corticosteroids, long-term oxygen therapy (LTOT), and daily airway clearance. The hospital course was favorable with PaCO₂ decreasing and marked symptomatic improvement; at three months he re-presented with recurrent purulent cough and again had P. aeruginosa in culture, prompting extended inhaled colistin and consideration of prophylactic macrolide therapy. This case underscores practical aspects of COPD–bronchiectasis overlap, highlights decision points around eradication strategies for P. aeruginosa, and illustrates the role of individualized, multidisciplinary follow-up aligned with GOLD 2025 and ERS guidance.